I Improving The Quality of Presentation of SMA Negeri 1 Anggaberi Below Knoster Plus Team Model (TKP) - Ishak Paway (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2020)
The purpose of this study is to improve the quality of the presentation of SMAN 1 Anggaberi by using the Team Knoster Plus Model. The purpose of using the Team Knoster Plus model is to improve the quality of school education services, especially regarding school performance, various participation, and good administration. The application of the Knoster Management Complex Change Team Model focuses on 5 components including(1) vision, (2) skills, (3) resources, (4) incentives, and (5) action plans. The concept of organizational leadership towards change with the management model recommended by the Knoster Team is proven to have positive implications for SMAN 1 Anggaberi: (a) the approach and policies taken and implemented in an organized manner are proven to be able to bring change and improve the quality of service and appearance of SMAN 1 Anggaberi; (b) strategic and action programs accompanied by the commitment of all school members show a significant change in organizational performance both academically and non-academically; (c) the application of a quality culture in school administration governance is proven to strengthen the accountability and capacity of schools as a public service organization; (d) a culture of appreciation as an approach in encouraging the performance and participation of school members has a positive impact on increasing school capacity and personnel productivity; and (e) participation and cooperation of all school members can build a positive impression of SMAN 1 Anggaberi externally.